Analisis Determinan Kinerja Karyawan pada PT. HATNI di Desa Tlogo Sadang, Paciran, Kabupaten Lamongan - Marinda, Ghin Uzdah; Mubarokah, Mubarokah; Harya, Gyska Indah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
In the competitive fishing industry, employee performance is the main factor in maintaining the productivity and competitiveness of the company. PT. HATNI, a fishery product processing company in Tlogo Sadang, Paciran, Lamongan, faces challenges in maintaining the quality and quantity of its production. This study aims to analyze factors that affect employee performance, including work ability, education level, work motivation, leadership style, job satisfaction, work environment, work loyalty, and work discipline. The method used was a quantitative approach with a survey of 60 employees selected using the purposive sampling technique, and data analysis was carried out by multiple regression using SPSS version 25. The results of the study show that all of these factors have a positive and significant influence on employee performance, with work loyalty and work discipline as the most dominant variables. In addition, a conducive work environment and an effective leadership style also increase employee motivation and satisfaction. The F test shows that independent variables simultaneously have a significant effect on employee performance, with an Adjusted R Square value of 77.6%, which means that most of the variations in employee performance can be explained by these factors. Therefore, PT. HATNI is advised to improve training programs, improve the motivation system, and create a better work environment to encourage employee productivity in a sustainable manner.